The imminence of death in question: the perspective of psychologists and clinical management of public health - Pfeifer, Paula M.; Palma, Cláudia M. S. (Medicina (Ribeirao Preto), 2009)
Study design: It is a qualitative research. Objective: To qualify the practice of the psychologist, that is, how they behave and work facing questions concerning death in the institutional context. Methods: Initially, it was carried out a survey on the number of psychologists who work in the health public system in Santa Maria establishing a sample of twelve professionals. Later, semi-structured and individual one-hour long interviews were conducted. The recorded interviews were transcribed and then read individually; highlighting the parts of speech that showed the way the psychologist develops his work and from the recurrence, some categories of analysis were elaborated, trying to articulate a group's view. The theoretical- psychoanalytic focus was used for the data analysis. Results: The results showed contradictions between the performance and positioning of the psychologist on the verge of death of a patient, with the predominance of individual characteristics in their act. Thus we could realize the danger of adopting a practice anyone can do, in the case of situations where there is not a specific handling, with stress in the dominance of individual characteristics. Conclusion: Although training in psychology does not have any specificity with regard to death, which imposes the professional some professional difficulties in situations of imminent death, these difficulties can be minimized since the psychologist has clearly defined - to himself and to the institution in which he works - what is his function, thus without missing his professional dimension. Moreover, it is reinforced the importance of the psychologist having his own personal therapy to be able to deal with those matters which demand his individual characteristics.